Risk and Prognosis of Secondary Rectal Cancer After Radiation Therapy for Pelvic Cancer - Yang, Runkun; Guan, Xu; Liu, Enrui; Wei, Ran; Zhao, Zhixun; Chen, Haipeng; Liu, Zheng; Yang, Ming; Jiang, Zheng; Wang, Xishan (Frontiers in Oncology, 2020)
Background: The relationship between pelvic radiation therapy (RT) and second primary rectal cancer (SPRC) is unclear. The aim of this study was to assess the risk and prognosis of SPRC after pelvic RT. Materials and Methods: Data for patients who had primary pelvic cancer (PPC) between 1973 and 2016 were retrieved from the Surveillance, Epidemiology, and End Results (SEER) database. Multiple primary standardized incidence ratios (SIRs) were used to assess the risk of SPRC. Five-year overall survival (OS) and rectal cancer-specific survival (RCSS) were calculated using Kaplan–Meier curves. Results: A total of 573,306 PPC patients were included, 141,225 of whom had been treated with RT. Primary cancers were located in the prostate (50.83%), bladder (24.18%), corpus uterus (16.26%), cervix (5.83%), and ovary (2.91%). A total of 1,491 patients developed SPRC. Overall, the patients who received RT were at increased risk of developing SPRC (SIR = 1.39, 95% confidence interval [CI]: 1.27–1.52). The risk of SPRC decreased in patients who did not undergo RT (SIR = 0.85, 95% CI: 0.80–0.91). The SIR for SPRC in patients who underwent external beam radiation therapy (EBRT) was 1.22 (95% CI: 1.09–1.36). The SIR for SPRC in patients who underwent a combination of EBRT and brachytherapy (EBRT–BRT) was 1.85 (95% CI: 1.60–2.14). For patients who received RT, the SIR for SPRC increased with time after a 5-year latency period from PPC diagnosis. The survival of RT-treated SPRC patients was significantly worse than that of patients with primary rectal cancer only (PRCO). Conclusions: Patients receiving pelvic RT were at an increased risk of developing SPRC. Different pelvic RT treatment modalities had different effects on the risk of SPRC. We suggest that long-term surveillance of SPRC risk is required for patients who have undergone pelvic RT, especially young patients.